Timing of Perioral Muscle Suppression in Smiled Speech - Liu, Yadong; Hung, Kyra; Villasenor, Melissa; Colcleugh, Shannon; Chung, Eunhee; Gick, Bryan (Canadian Acoustics, 2023)
During speech production, temporally overlapping movements can come into conflict. How such conflicts are resolved remains poorly understood. For example, during smiled speech, the simultaneous activation of facial expression and speech-related lip movements can generate oppositions between zygomaticus major (ZM) and orbicularis oris (OO) muscles; ZM activation pulls the lips apart for the smile, while OO activation pulls the lips together for lip closure and rounding movements [Stavness et al., 2013, JSLHR]. Previous research suggests that this conflict is resolved by suppression of either the smile or the lip closure movement [Liu et al., 2020, ISSP]. However, the mechanism by which one or the other movement is selected for suppression, or by which this suppression takes place, remains unknown. The present study aims to characterize the timing of the interaction that leads to this suppression, as well as the onset and length of suppression of smile when bilabial tokens are produced. All participants in this study were native English speakers between the ages of 18-25, instructed to read sentences featuring tokens (/m, f, v, b, p, w/) in three different postural conditions: neutral, smiling, and laughing. To measure the muscular “tug-of-war” between ZM and OO, electromyography (EMG) sensors were placed on the respective muscles, while simultaneous video recordings were processed using OpenFace 2.0 [Baltrušaitis et al., 2018, IEEE] to show corresponding facial action units of “lip corner puller” and “lip tightener” for each condition. Results and implications of these analyses will be discussed. OpenFace, a facial movement tracking tool, is used in this study to corroborate EMG measurements; as such, our results also provide evidence for the effectiveness of movement-based facial action units in reflecting muscle activity.